Broadening gender self‐categorization development to include transgender identities. Issue 1 (13th September 2022) - Jackson, Emma F.; Bussey, Kay
Abstract: Research on gender in psychology has increasingly affirmed diversity in gender, with recognition of binary and nonbinary transgender experiences. However, gender has been presumed to be cisgender (congruent with sex) and binary (either male or female) in classical developmental theories. In response, this review engages in a critical analysis of classical gender development theory informed by findings about gender from research on transgender identities. Under analysis was the concept of gender self‐categorization in classical theories of gender development including cognitive developmental theory, developmental gender schema theory, and social cognitive theory. Novel theoretical approaches are then outlined to situate recent advancements alongside classical theory. Conclusions are then drawn with brief recommendations for research methods that aim to include binary and nonbinary transgender participants. Drawing on the findings of this review it has been shown that gender self‐categorization is often implicitly presumed to be cisgender identification. To overcome this bias, it is suggested that greater attention to specific gender self‐categorization mechanisms are needed to open opportunities to include transgender experiences.